INVESTIGATION OF GEOMETRICAL DETERIORATION OF TRAMWAY TRACKS - Jover, V.; Gaspar, L.; Fischer, S. (Science and Transport Progress, 2020)
Purpose. The authors’ aim is to demonstrate their results of analysis of deterioration of tramway tracks’ geometry. Methodology. This article is a start of a PhD research. At first, the superstructure systems and the used instrument were summarized, after that the examination of running track, tramway stops, crossings and turnouts. Findings. The authors examined separately the running track, tramway stops, level crossings and turnouts. In case of examination of running track, we evaluated the measurement results according to two methods. To clarify the superstructure systems’ deterioration factor the authors had to do further measurements on other tramway lines too. Originality. The fulfilled analysis is the first step to the complex method that can consider and determine the optimisation of life-cycle costs of tramway superstructures. For this goal a lot of parameters, factors have to be taken into consideration in the future. There are available methods and models for different civil engineering areas, e.g. there is very complex methodology related to road pavements, but there is no special one related neither to railway tracks, nor tramway tracks. Practical value. The authors tried to construct a calculation and evaluation method that can assess the examined 6 different tramway superstructure types on the tramway line No. 1 in Hungarian capital (Budapest). It is a very new reconstructed tramway line that is the second longest one in Budapest. The authors showed which type of superstructure system is the «best» and the «worst» based on own made measurements and calculation-evaluation methods. The next aim of the authors is to start a PhD research in the Multidisciplinary Doctoral School at Szechenyi Istvan University (Győr, Hungary) with the continuation of this topic.